Simulasi Optimasi Green Energy Metode Photovoltaick Pada Gedung Rektorat Universitas Bina Bangsa Serang Banten - Bambang Setyo Panulisan; Dedy Khaerudin; Yolla Sukma Handayani; Siswanto Siswanto (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The simulation in this research investigates the possibility of using the walls of the rectorate building on the Bina Bangsa campus to install a wall area solar energy system. The building walls are simulated, becoming a representation of the walls of other buildings. PLTS electricity calculations use an interconnected Solar Power Plant [PLTS] system. Research shows that the building has a wall area of 10,353 m2 which can be used to install solar panels. The total electrical power produced in the area is 2030 kWp or 2.03 MWp. The power is divided into four, namely 630 kWp east of the roof, 535 kWp northwest, 668 kWp southwest and 553 kWp southeast.